Green Synthesis of Citrus sinensis Peel Extract-Mediated Ag-TiO2 and Its Application as a Photocatalyst for Organic Molecules and Antimicrobial Agent - Daniel Narh; Benjamin Sampson; Samuel Ocrah Junior; Gloria Pokuaa Manu; Benjamin Agyei-Tuffour; Emmanuel Nyankson; Johnson Kwame Efavi (Journal of Nanotechnology)
The growing focus on green chemistry and its application in nanomaterials has sparked a desire to explore more efficient and environmentally friendly synthesis methods. In this work, Citrus sinensis peel extract was used to synthesize silver-titanium dioxide, and the photocatalytic properties were evaluated in comparison with pristine titanium dioxide for wastewater purification and the antimicrobial efficacy tested. Titanium dioxide was coated with silver nanoparticles using weighted amounts of silver nitrate, with C. sinensis peel extract serving as the reducing agent. Characterization via X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy-energy dispersive spectroscopy, and ultraviolet-visible spectrophotometry confirmed silver-titanium dioxide formation. The maximum photodegradation rate was observed with a 1.5 wt.% silver-titanium dioxide composite using rhodamine B, proving it to be the most effective for organic molecule photodegradation. Subsequently, silver nanoparticles and silver-titanium dioxide demonstrated growth inhibition against strains of Staphylococcus aureus and Escherichia coli, highlighting their potential for wastewater treatment and microbial control.